Insights into the social life and obscure side of Scedosporium/Lomentospora species: ubiquitous, emerging and multidrug-resistant opportunistic pathogens. Issue 1 (January 2019) - Mello, Thaís P.; Bittencourt, Vera Carolina B.; Liporagi-Lopes, Livia C.; Aor, Ana Carolina; Branquinha, Marta H.; Santos, André L.S.
Abstract: The undeniable relevance of fungal infections caused by both yeasts and molds has considerably augmented over the last four decades, becoming a serious health public problem in hospitals worldwide. In this scenario, several fungal species have emerged as human pathogens able to cause diseases in both immucompromised and immunocompetent individuals. In this context, species belonging to the Scedosporium and Lomentospora genera are awakening global attention due to their ubiquitous distribution in human-impacted environments, multidrug–resistance profile and ability to cause severe and debilitating illnesses, which culminate in laborious and meticulous medical care, substantial treatment costs and high (and unacceptable!) morbidity and mortality rates. Together, these reasons have been stimulating the international scientific community to take a hard work in order to circumvent these undesirable situations. In this way, the researchers are trying to decipher the main physiopathological events behind the successful capacity of Scedosporium/Lomentospora species to escape from host immune attacks and to resist the available chemotherapeutic treatment options. Therefore, in an attempt to add some pieces to this puzzle, the present review compiles the main published data on taxonomy, genomic, ecology, diagnosis, epidemiology, clinical manifestations, relevant clinic-epidemiological statistics/metrics, current treatment options, promising alternative therapeutic approaches, expression of virulence attributes, in vitro interaction with phagocytic and non-phagocytic cells, in vivo animal infections and host immune defenses in the Scedosporium/Lomentospora field.